Pessimism as a contributory factor in equity premium puzzle : France and Germany - Lim, Joey Zu Er (Nanyang Technological University, 2021)
Abel (2002) revealed that with pessimism, the objective expectation is greater than the expectations of the consumers, thus conferring to a possible solution to the equity premium puzzle of Mehra and Prescott (1985). In this research study, we will focus on examining two countries belonging to the Eurozone — France and Germany. In order to trace the presence of pessimism and optimism, secondary data on the median point forecasts of Gross Domestic Product (GDP) growth in period 2000 to 2020 were retrieved and computed. Comparing the forecasted GDP growth rate with the actual GDP growth rates which were obtained from the World Bank, we discovered that the forecasts from International Monetary Fund (IMF) were generally pessimistic on the outputs for France and Germany. This results in an increase in the average equity premium, solving the equity premium puzzle. Further investigations were made to uncover the sources of pessimism in France and Germany. Some plausible explanations including rational learning, prevention of budget deficit or debt and commitment towards a prudent fiscal policy.